Influence of personality traits, self-esteem, and sense of coherence about motivation for the professional career of graduate students in accounting science - Anzilago, Marcielle; Daciê, Franciele do Prado; Sanches, Simone Leticia Raimundini (Education Policy Analysis Archives, 2022)
This study analyzes the influence of personality traits on professional career motivation from the mediation of the sense of coherence and self-esteem in stricto sensu graduate students in accounting science in Brazil. The research instrument consisted of a questionnaire with a 7-point Likert scale. A total of 208 valid responses were obtained, analyzed using the structural equation modeling technique. The results show that personality traits directly influence the motivation of academics in choosing to follow an academic career or not. The self-esteem variable mediated the relationship between personality traits and their motivation for a professional career. It is concluded that personality traits and career motivation are influenced by the sense of coherence and self-esteem. In addition to the theoretical contributions, which refer to the existing gap in the analysis of the three variables together, the study makes it possible to highlight two points for the members of postgraduate programs, which: the personality traits of students influence their decision to pursue a career academic professional, and; the situations experienced by these students during graduate studies (stresses, demands, stimuli, and recognition) can have an effect on their motivation and directly impact their strict sensu performance and their decision to continue or not in the academic area.